Models of Providing Employment for the Population and Possibilities of Using Them in Independent Conditions - Abdumalik Abdurahmonov Abdug'ani o'g'li (Zien Journals, 2022)
The main approaches to state participation in the formation of an employment policy are defined: 1) the participation of state bodies in regulating the labor market, during which they take on only those functions that cannot be performed using market mechanisms; 2) methods of active influence of the state on the sphere of managing the population’s employment. It is noted that state regulation of employment should be aimed at stimulating demand for labor and developing a set of measures that contribute to reducing the supply of labor. It is proposed that the employment policy of the population be directed, first of all, to a change in the nature of the labor market through the transition from excess employment with low labor productivity to a combination of low unemployment and over-productive employment. It is noted that the object of employment policy is not only officially registered unemployed, but also the entire able-bodied population. A definition of the concept of “state policy in the field of employment” is proposed. The fundamental directions of the state employment policy are structured and proposed. The state guarantees for the realization of the rights of citizens to work and social protection against unemployment are analyzed. We 92 believe that it is advisable to combine all types of employment guarantees in one chapter “State guarantees of employment”, in which it is necessary to determine the conditions for their implementation and the sources of financing. The types of guarantees for the intended purpose are proposed: guarantees of employment; material support for the unemployed; guarantees for employment and dismissal. According to population categories, guarantees are proposed to be differentiated into general, special and social. It is proposed, depending on the source of funding, to classify employment guarantees that are realized at the expense of: the state budget; local budgets; employers’ funds. A system for ensuring employment of the population is proposed, which is a set of government bodies and organizations implementing the population employment policy and includes various levels of management, the employment service, the regulatory framework and state guarantees of employment and protection against unemployment.
Keywords: state policy; population employment; labor market; unemployment